KILAS BALIK PENELITIAN KROMOSOM PALEM INDONESIA - Joko Ridho Witono (BERITA BIOLOGI, 2008)
There are 525 native palm species to Indonesia.Chromosome numbers of 61 Indonesian palm species have been reported,unfortunately, not all species were presented by their karyotype. Re-observation of palm chromosomes is needed, because mis identification of particular species and uncorrect chromosome counts might be happen in the past. Chromosome characteristics of some families, such as Poaceae and Onagraceae were proved useful for classification.On palms, almost all species within similar genera were known had similar chromosome numbers and different in chromosome forms and sizes.Trends to employ chromosome characteristics for palm classification is possible.Since, chromosome information on palm is limited,chromosome research has great challenge to do in the future.